Modern oncological classification of maxillary and mandibular defects, combined defects of the oral and maxillofacial region - A. P. Polyakov; I. V. Rebrikova (Опухоли головы и шеи)
After radical removal of regional tumors of the middle third of the face, defects of facial skeleton and adjacent anatomical structures in the maxillofacial region develop, including defects of the floor of the mouth, tongue, oropharynx, base of the skull, orbital tissues. Surgeons have proposed several classifications aimed at categorization of complexity and volume of the defects and promoting easier selection of the type of reconstruction. This article describes the main classifications of maxillary and mandibular defects. All classifications consider the problem from the point of view of a different practical approach, but most of them haven’t received wide acceptance. The available classifications do not fully take into account all components of the defects forming after surgical treatment of regional tumors. The authors propose a modification of the classification of maxillary defects by J. S. Brown and R. J. Shaw (2010). The modified classification should include not only bone defects but also other parts of the maxilla: epithelium, oropharynx, base of the skull, dura mater.The authors present a classification of mandibular defects based on the classification by M. L. Urken et al. (1991). The new classification includes notations of mandibular regions as well as extraskeletal components of defects of the lower third of the face. The authors distinguish anatomo-functional regions of the maxilla and mandibula and 3 complexity categories of defects of the facial skeleton. This allows to determine the necessity of single flap or complex reconstruction and its staging. The article also describes a classification developed at the P. A. Hertzen Moscow Oncology Research Institute – branch of the National Medical Research Radiological Center, Ministry of Health of Russia, which considers combined defects of the maxilla and mandibula and takes into account adjacent resected anatomical structures.The proposed classifications allow to categorize defects after resection of the maxillofacial area of any volume including removal of regional tumors, and promote optimal selection of the tactics of surgical reconstruction.